2021
DOI: 10.51458/bstd.2021.14
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota and Its Importance in Honey Bees

Abstract: In recent years, research on human and animal health has emerged as a very important microbiota and microbiome. Microbiota; has important functions in metabolism, immune system, growth and development. In recent years, it has been understood that the microbiota is effective in the protection of bee health in colony so prevent losses in honey bees. Season, flora, food sources, age of the individual, duties in the hive, chemicals used in the fight against parasites and pathogens, and many other factors can be ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 77 publications
0
4
0
1
Order By: Relevance
“…Honeybee microbiota is a complex ecosystem of microorganisms responsible for metabolic functions such as energy and vitamin management, satiety regulation, lipid homeostasis, and the adjustment of glucose levels [16]. It positively influences the immune system by regulating the induction of protective responses against pathogens and stimulates immune responses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Honeybee microbiota is a complex ecosystem of microorganisms responsible for metabolic functions such as energy and vitamin management, satiety regulation, lipid homeostasis, and the adjustment of glucose levels [16]. It positively influences the immune system by regulating the induction of protective responses against pathogens and stimulates immune responses.…”
Section: Introductionmentioning
confidence: 99%
“…It positively influences the immune system by regulating the induction of protective responses against pathogens and stimulates immune responses. The microbiota composition is unique to individuals within the same species [16]. Intestinal bacteria belonging to the honeybee microbiota are transmitted between individuals via trophallactic and oral-fecal transmission.…”
Section: Introductionmentioning
confidence: 99%
“…Many of the bee's functions depend on their gut microbiota. It is demonstrated that bee gut microbiota is involved in insect performance [8], resilience to stressors, and quantity and quality of bee-by products [2,8,14,21]. Acknowledging the above, bee gut microbiota hold the potential of a suitable implementation as a panel of biomarkers for effectively monitoring environmental pollution, besides sensing antimicrobial resistance diffusion and pathogenic traits transmission.…”
Section: Discussionmentioning
confidence: 99%
“…A specialised gut microbial community in honey bees plays a critical role in their growth and development and, subsequently, in the production of honey from nectar 20 . Dysbiosis of bee gut microbiome through environmental factors such as stress, diet, and antibiotic exposure increases the risk of pathogenic attack, leading to significant economic loss to apiarists 89 .…”
Section: Microbiome Databasesmentioning
confidence: 99%